Advocating for therapeutic recreation: is it just a matter of speaking up?. Issue 4 (2nd October 2022) - Park, Kathy; Rebecca Genoe, M.; Nelson, Sherri; Boser, Donna; Ostryzniuk, Linda; Cripps, Douglas G.
ABSTRACT: Therapeutic Recreation/Recreation Therapy continues to be misunderstood as a healthcare profession. Advocating for the profession and educating others about the role of Therapeutic Recreation/Recreation Therapy within the healthcare system is vital for dispelling myths and increasing awareness to ensure the best possible services are provided. In this mixed-methods study, we explore how Therapeutic Recreation/Recreation Therapy professionals advocate for their profession to better serve their clients and how they educate others regarding the role and benefits of Therapeutic Recreation/Recreation Therapy. Drawing on principles of Appreciative Inquiry, we conducted surveys ( n = 68) with Therapeutic Recreation/Recreation Therapy professionals, followed by 19 individual interviews and eight focus groups. Qualitative data were thematically analyzed. Respondents reported several misperceptions of Therapeutic Recreation/Recreation Therapy that persisted within their workplace. However, they also described the ways in which they cultivated awareness for Therapeutic Recreation/Recreation Therapy, including advancing the profession through structured efforts; daily efforts to promote Therapeutic Recreation/Recreation Therapy; educating others about Therapeutic Recreation/Recreation Therapy; and making the most of teachable moments. Despite their positive efforts to advocate for the profession, study respondents identified several challenges they faced in advocating for Therapeutic Recreation/Recreation Therapy. Recommendations for further development of advocacy efforts are considered.